Prevalence of Plantar Warts, Genital Warts, and Herpetic Infections in Greek Competitive Swimmers - Eleni Sfyri; Niki Tertipi; Vasiliki Kefala; Efstathios Rallis (Viruses)
Viral outbreaks are common in the sport community. Data regarding the prevalence of plantar warts, genital warts, herpes simplex type 1 (herpes labialis), herpes zoster, and genital herpes in competitive swimmers are lacking in the literature. The purpose of this study was to determine the prevalence of those viral infections among young competitive swimmers participating in Greek swimming clubs. Swimmers’ parents and adult swimmers were asked to complete an anonymous questionnaire. In total, 1047 swimmers enrolled in this study. The measured parameters included gender, age, times of infections, and seasons when athletes may be more susceptible to infections. Practicing information such as type of swimming facility, number of training years, average hours of daily training, behaviors in swimming practice, and sunlight exposure was also recorded. All infections showed a significant difference in relation to “age” and “years of training”. The gender significance was observed in herpes labialis (p = 0.016) and plantar warts (p = 0.05). The prevalence of all infections in swimmers who use outdoor facilities was higher. Certain behaviors such as walking barefoot on a pool deck and sharing swimming equipment correlate with herpes simplex and plantar warts. Virus infections can affect swimmers of all ages. In our study, plantar warts and herpes labialis are more common in swimmers. Herpes zoster and sexually transmitted viruses are rarer and affect adult swimmers. The impact of cutaneous infections on swimmers can affect performance and well-being. Effective prevention and management are essential to avoid complications. Proper hygiene, medical guidance, and treatment reduce swimmers’ exposure to skin viruses.